2022
DOI: 10.1109/tvt.2022.3158344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 5G Coexistence and Interference Signals in the C-Band Satellite Earth Station

Abstract: Satellite Services (FSS) used to be alone at the C-Band spectrum in most countries. Since the deployment of 5G in many countries (i.e., 3.3 -3.6GHz), FSS is not the exclusive system in the C-Band anymore. In order to minimize the detrimental interference for the FSS to allowable levels, regional exclusion zones of maximum radiated power in 5G base stations (BS) are proposed and evaluated.ixed Satellite Services (FSS) used to be alone at the C-Band spectrum in most countries. Since the deployment of 5G in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…However, we choose the frequency range 14.5–20 GHz, as the wavelength of this frequency range is very low (mostly 16–25 mm), and therefore the size of antenna is decreased, which is beneficial for communication and broadcasting satellites. 38 Terrestrial interference is absent in this frequency range. 39 Thus, combination of water, PPy–PDA and PPy resulted in polarisation loss, multiple reflections and scattering of the incident EMWs, as well as interfacial polarisation resulting from the presence of various interfaces, leading to an absorption dominated EMI shielding mechanism of the developed hybrid hydrogel.…”
Section: Introductionmentioning
confidence: 90%
“…However, we choose the frequency range 14.5–20 GHz, as the wavelength of this frequency range is very low (mostly 16–25 mm), and therefore the size of antenna is decreased, which is beneficial for communication and broadcasting satellites. 38 Terrestrial interference is absent in this frequency range. 39 Thus, combination of water, PPy–PDA and PPy resulted in polarisation loss, multiple reflections and scattering of the incident EMWs, as well as interfacial polarisation resulting from the presence of various interfaces, leading to an absorption dominated EMI shielding mechanism of the developed hybrid hydrogel.…”
Section: Introductionmentioning
confidence: 90%
“…As discussed in the introduction, an example of this is the allocation of the 3.3 -4.2 GHz band, which is commonly used for satellite communications, to 5G NR [16]. Various studies raised concerns regarding the interference at SGSs [17,18,19,20,21,60]. In a previous work, we focused on the cancellation of the SSBs of 5G as the irst step.…”
Section: C-band Interference At Sgssmentioning
confidence: 99%
“…Further research [18], [19] indicated that to avoid signi icant interference, a separation of over 15 km between the BSs and the SGSs is necessary. Authors in [20] and [21] demonstrated that even interference from adjacent band 5G signals can disrupt satellite services. Deploying a 5G NPN around our existing SGS will allow us to investigate the impact of the 5G to SGS interference and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we established the coexistence of 5G-BS and FSS-ES with 85 m distance as an interference source. Several studies, such as [11,12], have mentioned that C-band communications are seriously affected. Therefore, we installed filters on FSS-ES to determine if the interference coexistence of 5G-BS and FSS-ES affected the performance, and we addressed the interference coexistence.…”
Section: G-bs Interference Modelmentioning
confidence: 99%